2009
DOI: 10.1002/app.29800
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of fully biodegradable poly(lactic acid)/poly(butylene adipate‐co‐terephthalate) blends

Abstract: Both poly(lactic acid) (PLA) and poly(butylene adipate-co-terephthalate) (PBAT) are fully biodegradable polyesters. The disadvantages of poor mechanical properties of PLA limit its wide application. Fully biodegradable polymer blends were prepared by blending PLA with PBAT. Crystallization behavior of neat and blended PLA was investigated by differential scanning calorimetry (DSC), polarizing optical microscopy (POM), and wide angle X-ray diffraction (WAXD). Experiment results indicated that in comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 38 publications
5
75
0
7
Order By: Relevance
“…However, they found that the crystallisation rate coefficients of the blend membranes were higher than those of the original PLLA, suggesting that amorphous domains of PBAT serve as effective nucleation sites for PLLA. In their study, Xiao et al [17] observed that the degree of crystallinity of PLA in PLA/PBAT blends was markedly increased and there was found to be an increase in crystallisation rate with increase in PBAT content. Jiang et al [16] investigated recrystallization of both neat PLA and a PLA-5% PBAT blend.…”
Section: Crystallinity and Thermal Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, they found that the crystallisation rate coefficients of the blend membranes were higher than those of the original PLLA, suggesting that amorphous domains of PBAT serve as effective nucleation sites for PLLA. In their study, Xiao et al [17] observed that the degree of crystallinity of PLA in PLA/PBAT blends was markedly increased and there was found to be an increase in crystallisation rate with increase in PBAT content. Jiang et al [16] investigated recrystallization of both neat PLA and a PLA-5% PBAT blend.…”
Section: Crystallinity and Thermal Propertiesmentioning
confidence: 97%
“…For PLA, ΔH 100 = 93 J∕g and for PBAT, ΔH 100 = 114 J∕g [8,17], although, being a random co-polymer, PBAT does not crystallize to a great extent.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 98%
See 1 more Smart Citation
“…Even though the blends form two phases as reported by various authors, [ 1 , 2 ] partial miscibility has also been recently claimed since a DSC study reported a decrease of 4 ° C in the glass transition temperature ( T g ) of PLA when the blend contains 60% by weight PBAT. [ 3 ] …”
Section: Introductionmentioning
confidence: 99%
“…PLA have been blended with rubbers [3], thermoplastic starch (TPS) [4][5][6][7][8][9], poly(butylene succinate) (PBS) [10], poly(butylene succinate adipate) (PBSA) [11], poly(butylene adipateco-terephthalate) (PBAT) [12][13][14][15], acrilontryl-butadienestyrene (ABS) [16], polypropylene (PP) [17][18][19], and polystyrene (PS) [20,21], to obtain materials with lower cost and improved properties.…”
Section: Introductionmentioning
confidence: 99%